Developing Organizational Dynamic Capabilities in Project-Based integrated Solution: A Study of Servitization in Chinese Water treatment Industry - Shao, Hong Xiang (My University, 2019)
Manufacturing firms seeking to create and extend competitive advantage are striving to incorporate more services into their offerings. Although service is seen as service providers applying knowledge and skills for the benefits of customers, service providers are traditionally treated as pure decision takers, and their influence upon organizational dynamic capabilities is largely underestimated. There are research gaps such as how front-line service providers influence organizational dynamic capabilities and how organizational dynamic capabilities can be developed in servitization need to be systematically studied and explicitly explained. This study focuses on firms providing project-based integrated solutions. The attempt to fill identified research gaps is carried out by answering three questions: What roles the front-line service providers, project manager and team members, play in project-based integrated solution? How service providers can influence organizational dynamic capabilities in project-based integrated solution? What mechanisms service providers can adopt to develop dynamic capabilities in project-based integrated solution? The theoretical foundation of this thesis is built on dynamic capability and servitization literature, complemented by researches on project-based organizations. The empirical data are collected in semi-structured interviews. In this thesis, the strategic roles which project manager and team members play, and their respective influences upon organizational capabilities are differentiated. Meanwhile, the roles of service co-creators on customer side are studied and the influence on project performance are discussed. Overall, this study is qualitative in nature and the theory development follows a deductive in combination with inductive approach. This study creates multiple theoretical contributions. Knowledge about the roles of front-line service providers, their influence upon organizational capabilities, the micro-foundations of dynamic capabilities, and the influence of service co-creators in project-based integrated solution are developed. This study also generates insights for managers to reconsider firm organizational structure, decision-making processes, human resource and knowledge assets management in solution projects. Additionally, this study indicates that, to improve project performance, managers should emphasize the importance of service co-creators and develop their capabilities.
Keywords: Project-based integrated solution, Service Providers, Service Co-creators, Dynamic Capabilities, Micro-foundations, Mechanisms; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development